A right to home or an individual preference? The impact of the definition of home in international and European legislation on cases concerning Roma, Travellers, and Gypsies. Issue 1 (1st June 2022) - Cittadini, Silvia
Abstract : This article analyses how the concept of home is interpreted by the European Court of Human Rights and how its definition affects the decisions on cases concerning the Right to Home of Romani individuals. The analysis is conducted departing from a series of renowned cases that have been brought in front of the European Court by individuals of Romani origin. It has often been argued that these cases are steps towards the recognition of the Romani "special needs, " although such narrative has already been criticized for reproducing a stereotypical idea of Roma. In opposition to this argument and in light of the academic debate on the definition of the home, this article claims that the decisions of the Court are mainly based on the association between the home and a sense of stability, which fails to recognize other ideas of the home. The article, though, also highlights possible evolutions in the jurisprudence of the Court emerging from latter cases which may result in a reinforcement of the housing rights of these groups.